NUTRITION IN THE PROPHYLAXIS OF ORAL AND DENTAL INJURIES - REVIEW - Liviu Gavrilă-Ardelean; Mihaela Gavrilă-Ardelean; Agnes K.Lackner; Doriana Agop-Forna; Andrei Kozma (Romanian Dental Association for Education, 2021)
Contemporary human diet is a major cause of tooth decay and other systemic diseases, such as diabetes, obesity and cardiovascular disease. Since the quantitative relationship between food principles is an important prophylactic factor of health, qualitative research in the form of theoretical review of specialty literature and experimental case studies has been carried out, with the aim of highlighting the roles of food principles for the prophylaxis of oral lesions, tooth decay and general oral health. The conclusions converge to the unsurprising perspective that the lack of dietary principles, the lack of proteins, for example, during the development of dental enamel matrix, favors the appearance of caries, while an excess of lipids decrease their incidence. Exogenous prophylaxis through diet of tooth decay is achieved by eating foods with increased consistency, which have a mechanical brushing role. Diet must be balanced by dietary principles: low in refined sugars and rich in vitamins, minerals and fluoride. Beyond the specialized elements, the present review is also addressed to the education of the population group of parents, educators, pedagogues, institutional paediatric care staff, but also to other categories of interest, through the fundamental knowledge of the correct, healthy diet of children, for prophylactic purposes for their oral health.